Prevalence and Related Psychological Aspects of Frailty in Hemodialysis Patients - Natashia, Dhea; Irawati, Diana; Purwati, Nyimas Heny; Rahmi, Upik; Narawangsa, Asri; Handayani, Roswati; Heriadi, Ronny (Jurnal Keperawatan Muhammadiyah, 2024)
Objective: This study aimed to ascertain the prevalence of frailty and associated psychological factors among hemodialysis patients. Methods: A cross-sectional study was conducted employing a convenience sample of CKD patients undergoing hemodialysis at a Jakarta hospital. A total of 151 participants were included in this study. Instruments included demographic and clinical characteristics. The Tilburg Frailty Indicator (TFI) assessed frailty, while the Self-Rating Depression Scale (SDS) and Self-Rating Anxiety Scale (SAS) evaluated psychological status. Data analysis encompassed univariate descriptive statistics, t-test, and Pearson correlation to identify the relationship among variables. A multivariate regression analysis studied frailty index associations with demographic, clinical, and psychological factors. Results: Results: This study indicates that the prevalence of frailty, assessed by the Tilburg Frailty Index (TFI), is 53.6%, primarily evident in the physical aspect. Positive correlations are found between frailty and age, unemployment, higher CCI, and a history of diabetes. Anxiety is correlated with female gender and a history of diabetes, while depression correlates with age, female gender, higher CCI, and a history of diabetes. Conclusion: The study highlights the complexity of frailty among hemodialysis patients. Significant correlations emerged, associating frailty with factors such as age, unemployment, comorbidity, and a history of diabetes. Frailty was linked to psychological aspects, specifically anxiety and depression. Tailored interventions are recommended, focusing on early identification, psychological support, and a holistic care approach. Educational initiatives for healthcare providers are crucial to enhance awareness and improve the quality of care for this vulnerable population, leading to better health outcomes.